Effect of supplementation with linseed or a blend of aromatic spices and time on feed on fatty acid composition, meat quality and consumer liking of meat from lambs fed dehydrated alfalfa or corn. (May 2017) - Realini, C.E.; Bianchi, G.; Bentancur, O.; Garibotto, G.
Abstract: Cross-bred lambs ( n = 72) were fed finishing diets using a factorial arrangement of treatments: BASAL DIET (alfalfa pellets or corn), SUPPLEMENT (none, linseed or aromatic spices), TIME ON FEED (41 or 83 days). Carcass and meat quality traits, fatty acid composition, color stability and consumer liking were determined. Feeding alfalfa improved sensory ratings and fatty acid composition of lamb. However, corn or longer alfalfa feeding would be recommended if heavier and fatter carcasses are sought. Consumer liking and fatty acid composition of lamb were improved with addition of spices and linseed, respectively. But additional antioxidant strategies should be considered to delay meat color deterioration during storage if lambs are fed corn-linseed for 83 days. Although alfalfa basal diet and linseed supplementation improved fatty acid composition, feeding the basal diets for at least 41 days resulted in low n -3 fatty acid concentrations in muscle. Highlights: Alfalfa improved lamb sensory ratings and fatty acid composition relative to corn. Corn or longer alfalfa feeding is recommended for heavier and fatter carcasses. Spices addition improved liking scores and linseed the nutritional quality of lamb. Feeding corn and linseed for 83 d may require extra antioxidants for color stability. Feeding concentrates for at least 41 d did not result in meat as a 'source of n -3'.